Vendor Selection Analysis Based on AHP to Enhance Service Quality and Consumer Satisfaction at PT XYZ - Nur Aini Alhamda; Pebi Yuda Pratama; Meta Nidya Putri; Aurelius Listone Fernandez; Hizba Muhammad Sadida (Journal of Logistics and Supply Chain, 2022)
In the midst of intense economic competition, all companies are required to improve their performance in order to maintain their existence in the business world. Not only must they be able to produce high-quality goods, but the company must also be able to provide extraordinary service to its consumers, especially companies engaged in logistics. One way to achieve the best service aspects is through selecting the right freight forwarding vendor. This study aims to determine the best vendor for PT. XYZ based on the most appropriate criteria using the Analytic Hierarchy Process (AHP) method. The qualitative method with a descriptive approach is the method used in writing this article with the results showing that the criteria that have the highest rating weights are the level of service criteria with 47%, the location criteria with 26%, the responsiveness criteria with 19% and the price criteria with 8%. After considering these four criteria, the sequence of vendors with the highest priority value is Vendor E with a total priority value of 0,59. Meanwhile, Vendor D and Vendor F occupy the second and third positions with a total priority score of 0,57 and 0,54.